BEYOND THE ARAB SPRING: FLAKES OF PRE-NATION-STATES HISTORICAL HERITAGE OF THE ARABS - MUHAMMAD ABDILLAH IHSAN (STIT DARUL ULUM KOTABARU, 2024)
This article talks about the Arab Spring phenomenon using a different perspective. The author tries to guide the historical factors of the formation of nation-states in the Middle East and North Africa after the collapse of the Ottoman Turkish Empire with various factors that have a significant influence. Moving on from the failure of the unity of the Ummah which was carried out by the spirit of Pan-Islamism of the Ottoman Turks, which was followed by the failure of Pan-Turkism and Pan-Arabism, brought the Muslim community into the trap of narrow nationalism that was regionalistic and very tribal, group, and sectarian. These tribal, group, and sectarian fragments have a big contribution in creating the pre- and post-Arab Spring conditions that haven't found the dream; democratization, non-discrimination, and social and economic equality. Another assumption, Islam, as the main religion of Arab society, gives a positive response, or at least passively for the continuation of narrow nationalism which is identical to the interests of small groups and is contrary to the spirit of the unity of the ummah. This research uses a qualitative approach with a case study method to explore processes, activities, and events. The data data taken from relevant documents and uses a holistic analysis technique by narrative-descriptive approach. In the end, this research concludes the typical tribalist and sectarian Arab culture and historical factors contributed to the gaps in Arab society which culminated in the Arab Spring.